Nongranulomatous Anterior Uveitis Associated With Alendronate Therapy - Salmen, Siham; Berrueta, Lisbeth; Sánchez, Nelly; Borges, Lérida (Investigación Clínica, 2009)
We describe a case of acute nongranulomatous anterior uveitis associated with alendronate therapy, in an adult woman, without medical history of previous diseases, except for intercurrent problems of osteoporosis. The symptoms disappeared abruptly after anti-inflammatory therapy and discontinuation of alendronate. Side effects associated with ocular inflammation have been recently documented in 3 patients under alendronate therapy. Clinical and laboratory diagnosis of ocular inflammation syndromes are also reviewed